A Study on Residents’ Willingness for Tourism Ecological Compensation and Its Influencing Factors: A Case Study of Zhujiawan Village in the Qinba Mountain Region - Wang, Wei (International Journal of Global Economics and Management, 2024)
Ecological compensation plays a crucial role in balancing stakeholder interests, aligning with the principles of ecological civilization and sustainable development. However, research on tourism ecological compensation, especially concerning community residents’ perspectives, remains limited. This study addresses this gap by examining the case of Zhujiawan Village in China’s Qinba Mountain region. Through surveys and analysis, the study investigates community residents’ perceptions, preferences, and factors influencing their willingness to accept tourism ecological compensation. The findings reveal that while residents acknowledge the positive economic impacts of rural tourism development, they also express concerns about environmental pollution, particularly waste and noise. They largely attribute responsibility for ecological compensation to the government and tourism developers. Cash compensation emerges as the preferred method, with employment opportunities also valued. Additionally, residents expect an annual compensation standard of 1,033 RMB, influenced by their satisfaction with the local ecological environment and awareness of ecological compensation policies. The study highlights the importance of balancing economic development with environmental protection in rural tourism destinations. It underscores the need for diversified compensation mechanisms and emphasizes the significance of community involvement in decision-making processes for sustainable tourism development.